Clemente Palma's intervention in the 1909 San Marcos debate on the education of the "Indian" - Heredia Neyra, Juan José (2024)
The Peruvian intellectual Clemente Palma, considered the most important disseminator of scientific racism in Peru, participated in the controversy of April 1909, which revolved around the value of education in the potential transformation of the Peruvian indigenous people. Clemente Palma, after his 1897 thesis was referenced by Pedro Zulen, intervened in the debate denying the indigenous people the capacity for education. On the contrary, he proposed that the mestizo from the coast and the criollo are the only ones capable of being educated. Thus, they would no longer be exploiters and would treat the indigenous people well. The latter should subordinate themselves to the former, given that their intellectual capacities are limited. The controversy evaluates the continuities and changes regarding what he supported in 1897 in his thesis "The Future of Races in Peru".